HUBUNGAN FREKUENSI PEMBERANTASAN SARANG NYAMUK DAN ANGKA BEBAS JENTIK DENGAN KEJADIAN DEMAM BERDARAH DENGUE PADA PERIODE JANUARI-DESEMBER TAHUN 2012 DI KOTA MEDAN - Sondang Pasaribu; devi nuraini santi; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Abstract The relation of the frequency eradication of mosquito breeding place and larvae-free index with the incidence of dengue hemorrhagic fever in the period January to December 2012 in the city of Medan. Dengue hemorrhagic fever (DHF) was a public health problem in Indonesia. Medan was dengue endemic area. DHF had not been able to be controlled optimally. Various ways of prevention and eradication done to tackle the occurrence of dengue fever, including Eradication of Mosquito Breeding Place (EMBP) and Larva Periodic Inspection. Research sites in Medan with the sample is the entire data 39 health centers. This study used a mixed ecological study design was based on place and time. Data analysis was performed using univariate and bivariate analysis using correlation test. The results based on bivariate analysis with a level of 95%, obtained statistical results that there is no significant relationship between the eradication of mosquito breeding with DHF based on the level of health centers (p=0,754) and in the period from January to December (p=0,754), and there is no significant relationship between larvae-free index with DHF based on the level of health centers (p=0,619) and the period of January to December (p=0,800). Based on the research results, it was concluded that there was no correlation between the frequency of eradication of mosquito breeding place and larvae-free index with the incidence of DHF. Eradication of mosquito breeding place and larva periodic inspection should be done continuously and need socialization to increase community participation. Keywords: DHF, EMBP, larvae-free index.